Improvement of Designing Laboratory Scale Plastic Chopping Equipment with the TRIZ Method (Theorija Rezhenija Izobretatelskih Zadach) - Fijra, Rafiqa; Saleh , Zulkiffli; Rifqi Adinugraha , M.; Hastarina, Merisha; Wahyudi, Bayu (Publisher Cv. Inara, 2022)
The practical use of plastic increasing the demand for plastic. Plastic waste is difficult to decompose, currently many efforts have been made to reduce this plastic waste. A plastic chopping machine is a tool used to produce shredded plastic items into small pieces of a certain size, which can later be used for further processing as a recycling effort. This study improves the design of an existing plastic chopper that focuses on increasing reliability and convenience by the user. The analysis was carried out using a fishbone diagram and the TRIZ design method. The research resulted in a number of causes for the emergence of problems in the operation of the plastic chopper and a new design for the tool, namely improvements in terms of the type of blade, type of motor, and size of the tool. Keywords: Improvement designing, plastic chopper, fishbone diagram, and TRIZ method.